2022
DOI: 10.7759/cureus.24071
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Distance Learning, Stress Level, and Perceived Quality of Education in Medical Students After Transitioning to a Fully Online Platform

Abstract: Background: Before COVID-19, preclinical medical students traditionally attended didactic lectures in inperson settings. Due to social distancing, students were required to switch to online meeting platforms, such as Zoom. For medical students accustomed to in-person interactions, these changes may add more stress to the already stressful medical school experience. Furthermore, it was unclear if students' stress levels were related to their preference for one learning modality over another. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The variables were entered in the following order: demographics to control for confounding of variables that may be associated with e-learning satisfaction (Block 1); followed by stress, health-related quality of life (H-RQoL: Summary Index of Unhealthy Days), and social presence (Block 2), which has been evidenced in other research to be associated with e-learning satisfaction [20,33,48] brief-coping subscales (Block 3), which were explored as new elements in this article. For the model regression coefficients, 95% CI, F statistics, R2, and change in F and R2 are reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables were entered in the following order: demographics to control for confounding of variables that may be associated with e-learning satisfaction (Block 1); followed by stress, health-related quality of life (H-RQoL: Summary Index of Unhealthy Days), and social presence (Block 2), which has been evidenced in other research to be associated with e-learning satisfaction [20,33,48] brief-coping subscales (Block 3), which were explored as new elements in this article. For the model regression coefficients, 95% CI, F statistics, R2, and change in F and R2 are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that overall e-learning quality has a significant positive impact on student satisfaction and intentions to continue usage of e-learning platforms [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Dengan adanya penurunan dari perjalanan menuju kampus ini disertai dengan kemudahannya untuk dapat mengikuti pembelajaran di rumah menghasilkan penurunan dari kelelahan yang dialami dari mahasiswa tersebut. Walaupun begitu terdapat masalah dengan adanya perkuliahan secara online dapat memberikan masalah kepada mahasiswa dengan adanya memengaruhi keterlibatan dari mahasiswa tersebut dalam kelas, serta dapat menimbulkan masalah teknis yang dapat mengganggu belajar dari mahasiswa sehingga dapat memberikan stres kepada mahasiswa tersebut (15).…”
Section: Karakteristikunclassified
“…Furthermore, the inherent rigor of the curriculum and extended clinical practices cause medical students to grapple with heightened levels of mental and physical stress, often more than peers in other academic fields (Tennant et al, 2007 ; Rotenstein et al, 2018 ; Afshar et al, 2022 ; Slimmen et al, 2022 ). The advent of the COVID-19 pandemic only added to this stress, triggering a widespread shift to distance learning, and prompting medical institutions to re-evaluate traditional teaching methods (Khalil et al, 2020 ; Afshan et al, 2022 ; Altaf et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%